The demographics of defense and security in Japan - Bravo, Jorge Miguel (2022)
Bravo, J. M. (2022). The demographics of defense and security in Japan. In Á. Rocha, C. H. Fajardo-Toro, & J. M. R. Rodríguez (Eds.), Developments and Advances in Defense and Security: Proceedings of MICRADS 2021 (pp. 359-370). (Smart Innovation, Systems and Technologies; Vol. 255). Springer. https://doi.org/10.1007/978-981-16-4884-7_29